1996
DOI: 10.1086/177089
|View full text |Cite
|
Sign up to set email alerts
|

The H i Content of Spirals. I. Field Galaxy H i Mass Functions and H i Mass--Optical Size Regressions

Abstract: A standard parametric maximum-likelihood technique is used to determine both the probability distribution over total HI mass M HI and the regression of this quantity on the linear optical diameter D o for eld giant spirals (Sa-Sc) from a complete HI-ux-limited data set of these objects. This sample is extracted from a subset of the optical magnitude-limited Catalog of Galaxies and Clusters of Galaxies comprised of galaxies observed in the 21 cm HI line and located in the lowest density environments of the Pisc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
153
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(163 citation statements)
references
References 33 publications
8
153
2
Order By: Relevance
“…Here, combining isolated LTGs from the Local Supercluster with the lowest density objects in the Coma supercluster we obtain C 1 = 7.50 and C 2 = 0.79, consistently with the Local Supercluster alone (and with the Coma1 cloud, see Boselli & Gavazzi 2009). These coefficients are consistent with those adopted by Solanes et al (1996) up to Sc galaxies, and by Toribio et al (2011) up to Scd-Sd galaxies. Figure 3 shows the relations among M HI and the diameters found adopting these coefficients.…”
Section: Pattern Of Hi-deficiencysupporting
confidence: 89%
See 2 more Smart Citations
“…Here, combining isolated LTGs from the Local Supercluster with the lowest density objects in the Coma supercluster we obtain C 1 = 7.50 and C 2 = 0.79, consistently with the Local Supercluster alone (and with the Coma1 cloud, see Boselli & Gavazzi 2009). These coefficients are consistent with those adopted by Solanes et al (1996) up to Sc galaxies, and by Toribio et al (2011) up to Scd-Sd galaxies. Figure 3 shows the relations among M HI and the diameters found adopting these coefficients.…”
Section: Pattern Of Hi-deficiencysupporting
confidence: 89%
“…The coefficients C 1 and C 2 were determined by Haynes & Giovanelli (1984) by studying a control sample of isolated objects, and later, on a larger sample by Solanes et al (1996). Both samples are composed almost exclusively of giant spirals however.…”
Section: Pattern Of Hi-deficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…where the mean hybrid H I surface density is obtained from the ratio of the integrated H I flux density S H I of the galaxy in Jy km s −1 and its apparent optical diameter a in arcminutes (Solanes, Giovanelli & Haynes 1996):…”
Section: Gas Contentmentioning
confidence: 99%
“…A better estimate of the effect of the cluster environment on the H i content of the Norma spiral galaxies is the H i deficiency parameter (Giovanelli & Haynes 1985) which compares the H i content of a cluster galaxy with the average H i content of an isolated field spiral of the same morphological type. Solanes et al (1996) have shown that the H i content of a field spiral also depends on the diameter. However, due to the uncertainties in diameter of our highly obscured galaxies we have not included the diameter dependence in our calculations.…”
Section: Hi Deficiency In the Norma Clustermentioning
confidence: 99%